Ar-plasma activated Au film with under-coordinated facet for enhanced and sustainable CO2 reduction to CO. Issue 54 (December 2021) - Woldu, Abebe Reda; Wang, Yanjie; Guo, Lingju; Hussain, Sajjad; Shah, Aamir Hassan; Zhang, Xuehua; He, Tao
Graphical abstract: Au film treated by Ar plasma exhibits improved activity and selectivity for electrocatalytic reduction of CO2 to CO, which is mainly due to the formation of low-coordinated Au(311) facet and nanostructuring of the Au films. Highlights: Nanostructuring Au film treated by Ar plasma results in decrease in work function. Plasma treatment can lead to formation of under-coordinated Au(311) sites. Plasma treatment can increase electrochemical active surface area of Au film. Au(311) exhibits higher performance in CO2 activation than Au(111). A high FECO of 81.4 % is achieved using a solar cell as the external power source. Abstract: Au exhibits special properties in electrocatalytically converting CO2 into CO, wherein it is challenging to improve the activity and selectivity of CO production due to concurrent H2 evolution reaction. Since nanostructured Au films with under-coordinated facets can facilitate catalytic performance in selective CO2 reduction, herein, we develop a facile method to bombard the Au films using Ar plasma to induce the surface nanostructure, which exhibit greatly enhanced activity and selectivity of reducing CO2 to CO, with a Si solar cell as the power source in order to achieve green conversion of CO2 . A high CO Faradaic efficiency of 81.4 % is achieved, with a cathodic CO energy efficiency of 58.0 % at –0.65 V vs RHE. It is found that the Ar-plasma treatment can create new active sites of under-coordinated facet with open structure, Au(311), lower surface work function, and increase the electrochemical surface area of Au film. Density functional theory calculations reveal that the Gibbs free energy required for COOH* formation is lower on the open Au(311) facet than that on the closely-packed Au(111), accounting for greater ability of the CO2 activation on Au(311) facet. All these are favorable for enhanced CO2 conversion to CO.